Urban Fishing as Informal Leisure and Psychosocial Coping: A Case Study from Bandung, Indonesia - Pratama, Obi (Universitas Bojonegoro, 2025)
This study explores urban fishing as a form of informal leisure and psychosocial coping among residents in Bandung, Indonesia. Employing a mixed methods approach, data were collected through a survey of 60 respondents and in-depth interviews with 15 participants. The findings reveal that most participants engage in fishing to find calm, alleviate stress, and foster social connection. Fishing commonly takes place in informal urban spaces such as riverbanks and community ponds, indicating a grassroots reappropriation of urban space beyond official planning. The analysis draws on theories of informal leisure (Stebbins), everyday practice (de Certeau), non-clinical emotional coping (Lazarus & Folkman), and the capabilities approach in human development (Sen & Nussbaum). The study concludes that urban fishing functions as a strategic practice for psychosocial resilience, social cohesion, and spatial negotiation in the urban environment. It recommends that policymakers recognize informal recreational practices as part of inclusive, human-centered urban development.